PEMAKNAAN RASISME DALAM FILM (ANALISIS RESEPSI FILM GET OUT) - Adlina Ghassani; Catur Nugroho (Jurnal Manajemen Maranatha, 2019)
Movie is one form of mass communication media which often enjoyed by people. The movie Get Out that is directed by Jordan Peele shows about how is the act of white people discrimination towards black people. This research uses the qualitative method with descriptive type and uses Stuart Hall’s reception analysis approach. Reception analysis views the active audiences which are the viewers and readers to produce and reproduce the meaning in an impression of a media. The purpose of this research is to describe audiences’ interpretation and to know the position of the audiences according to Stuart Hall’s three readership position towards the movie Get Out that shows racism. This research uses paradigm of constructivism. The result of this research shows that audiences meaning of the movie Get Out towards the four informants generates different meaning and out of seven scene analysis units studied, the audiences’ position in their acceptance of the racism in the movie Get Out is dominated by oppositional position. There are also some informant that are in dominant hegemonic position. Where in each scene contains different racism material. Keywords: Communication; Reception Analysis; Film